SidF, a dual substrate N5-acetyl-N5-hydroxy-L-ornithine transacetylase involved in Aspergillus fumigatus siderophore biosynthesis - Thanalai Poonsiri; Jan Stransky; Nicola Demitri; Hubertus Haas; Michele Cianci; Stefano Benini (Journal of Structural Biology: X)
Siderophore-mediated iron acquisition is essential for the virulence of Aspergillus fumigatus, a fungus causing life-threatening aspergillosis. Drugs targeting the siderophore biosynthetic pathway could help improve disease management. The transacetylases SidF and SidL generate intermediates for different siderophores in A. fumigatus. A. fumigatus has a yet unidentified transacetylase that complements SidL during iron deficiency in SidL-lacking mutants.We present the first X-ray structure of SidF, revealing a two-domain architecture with tetrameric assembly. The N-terminal domain contributes to protein solubility and oligomerization, while the C-terminal domain containing the GCN5-related N-acetyltransferase (GNAT) motif is crucial for the enzymatic activity and mediates oligomer formation. Notably, AlphaFold modelling demonstrates structural similarity between SidF and SidL. Enzymatic assays showed that SidF can utilize acetyl-CoA as a donor, previously thought to be a substrate of SidL but not SidF, and selectively uses N5-hydroxy-L-ornithine as an acceptor.This study elucidates the structure of SidF and reveals its role in siderophore biosynthesis. We propose SidF as the unknown transacetylase complementing SidL activity, highlighting its central role in A. fumigatus siderophore biosynthesis. Investigation of this uncharacterized GNAT protein enhances our understanding of fungal virulence and holds promise for its potential application in developing antifungal therapies.